The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.resuscitation.2019.06.280
|View full text |Cite
|
Sign up to set email alerts
|

The presence of psychological trauma symptoms in resuscitation providers and an exploration of debriefing practices

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 35 publications
1
47
0
Order By: Relevance
“…The same results were obtained by Firdousa (2017), who observed that more than 50 percent of emergency nurses are exposed to high stress because of their work demands. Spencer et al (2019) report that nearly 10 percent of acute care staff screened positive for PTSD as a result of attending in-hospital cardiac arrest situations, and an addtional 47 percent of staff declared symptoms of trauma, with junior staff being at highest risk of developing trauma symptoms. Furthermore, very few debriefs take place after resuscitations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The same results were obtained by Firdousa (2017), who observed that more than 50 percent of emergency nurses are exposed to high stress because of their work demands. Spencer et al (2019) report that nearly 10 percent of acute care staff screened positive for PTSD as a result of attending in-hospital cardiac arrest situations, and an addtional 47 percent of staff declared symptoms of trauma, with junior staff being at highest risk of developing trauma symptoms. Furthermore, very few debriefs take place after resuscitations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, negative impacts of a debrief session were uncommon. The most frequent reason for finding the debrief a negative experience was the debrief being poorly organized (12,9 percent) (Spencer, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…New research suggests that PTSD in resuscitation providers at baseline is 9.6%. 23 The risk of PTSD for front line staff in this pandemic may therefore be greater than 10%.…”
Section: How Staff May Experience Stress During a Pandemicmentioning
confidence: 99%